Analysis of the Quality Health Services on Dental Poly Patient Satisfaction at Drs. Haji Amri Tambunan Regional General Hospital, Deli Serdang - Arlita Jemima BR.Surbakti; Chrimis Novalinda Ginting; Santy Deasy Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Patient satisfaction will encourage high utilization of health services. Patient satisfaction is one of the measures of service quality that will determine hospital performance. Quality and patient satisfaction is one of the factors that make patients come back for treatment because of the feeling of satisfaction they receive or even never come again. This study aims to evaluate the quality of medical services by examining the following dimensions: tangible evidence, reliability, timeliness, confidence, and compassion towards the well-being of dental clinic patients at Haji Amri Tambunan Regional General Hospital. Analytic survey methodology with a cross-sectional design was used in this study. With a sample size of 377, the study population consisted of all dental clinic patients at the Haji Amri Tambunan Regional General Hospital in Deli Serdang from July to December 2023, totaling 1,543 people. Questionnaires were used to collect data, and the Chi-Square test was used to statistically test the findings. Based on the results of the study, it can be stated that there is a significant relationship between the quality of health services based on the dimensions of physical evidence (tangibles) (p-value=0.000), reliability (p-value=0.001), responsiveness (p-value=0.034), assurance (p-value=0.037), and empathy (empathy) (p-value=0.005) to patient satisfaction. Dental polyclinic patient satisfaction is most influenced by the physical evidence variable which is one aspect of health service quality. The dimension of responsiveness is the best dimension of health service quality, while the dimension of physical evidence has the most dominant influence on dental polyclinic patient satisfaction, it is hoped that the Haji Amri Tambunan Deli Serdang Regional General Hospital can improve the reliability dimension, namely providing services as promised accurately and reliably. Keywords: Quality of Health Services, Responsiveness Dimension, Patient Satisfaction